Sphingomonas cremea sp. nov., isolated from ginseng soil. Issue 3 (31st March 2023) - Park, Yuna; Liu, Qingzhen; Maeng, Soohyun; Oh, Hyejin; Yun, Chan-Seok; Choe, Hanna; Lee, Hyang Burm; Im, Wan-Taek
Abstract : A novel Gram-stain-negative, aerobic, rod-shaped, non-motile, cream-coloured strain (G124 T ) was isolated from ginseng soil collected in Yeongju, Republic of Korea. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain G124 T belongs to a distinct lineage within the genus Sphingomonas (family Sphingomonadaceae, order Sphingomonadales and class Alphaproteobacteria ). Strain G124 T was closely related to Sphingomonas rhizophila THG–T61 T (98.5 % 16S rRNA gene sequence similarity), Sphingomonas mesophila SYSUP0001 T (98.3 %), Sphingomonas edaphi DAC4 T (97.6 %) and Sphingomonas jaspsi TDMA–16 T (97.6 %). The strain contained ubiquinone 10 as the major respiratory quinone. The major polar lipid profile of strain G124 T comprised phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine and sphingoglycolipids. The predominant cellular fatty acids of strain G124 T were summed feature 8 (C18 : 1  ω 7 c /C18 : 1  ω 6 c ; 33.4 %), summed feature 3 (C16 : 1  ω 6 c /C16 : 1  ω 7 c ; 27.2 %) and C16 : 0 (18.3 %). The genome size of strain G124 T was 2 549 305 bp. The genomic DNA G+C content is 62.0 mol%. The average nucleotide identity and digital DNA–DNA hybridization values between strain G124 T and other Sphingomonas species were in the range of 71.2–75.9 % and 18.7–19.9 %, respectively. Based on the polyphasic analysis such as biochemical, phylogenetic and chemotaxonomic characteristics, strain G124 T represents a novel species of the genus Sphingomonas, for which the name Sphingomonas cremea sp. nov. is proposed. The type strain is G124 T (=KACC 21691 T =LMG 31729 T ).